Limits of detection of Magnaporthe oryzae Triticum pathotype in wheat seed: implications for pathogen dissemination - Kiyuna, Javier (Kansas State University, 2020)
Wheat blast is an emerging disease on wheat, caused by the seed-borne fungal pathogen Magnaporthe oryzae Triticum pathotype (MoT). The first objective of this research was to establish the detection threshold for MoT in infected wheat seeds as a function of sensitivity and specificity of a modified quantitative and conventional PCR assay. Accurate amount mix ratios of MoT colonized ground seeds / non-MoT colonized ground seeds were stablished with different MoT severity and incidence gradient ratios. Disease severity and incidence gradients were verified by end-point PCR and q-PCR. To further verify sensitivity and specificity in the presence of potentially interfering DNAs, gradients based on ten-fold serial dilutions of MoT DNA were established with genomic M. oryzae populations DNA and wheat seed DNA. The detection threshold from the end-point PCR was 0.1% of MoT colonized seeds in a seed sample as a function of disease incidence. The detection threshold varied as a function of disease severity for MoT-colonized seeds; the minimum MoT detectable by end-point PCR was 3 x 10³ MoT cells/seed. This study verified the specificity to discriminate the Triticum pathotype from other M. oryzae pathotypes as well as demonstrated no interference from wheat seed DNA. This study provides evidence that to establish pathogen detection thresholds in plant seed, both disease incidence and severity must be evaluated to reduce the probabilities of false negatives. The second objective was to develop a preliminary risk assessment tool as a guide to minimize the probability of disseminating MoT-infected seeds. A field survey of commercial wheat production farms in Bolivia was conducted during a MoT epidemic year. The effects of planting dates and cultivar susceptibility on disease severity were determined. The preliminary risk assessment tool was based on weather conditions during an epidemic and non-epidemic year, previously published studies on MoT infection of wheat seeds during epidemics, detection thresholds by Blotter seed test and PCR tests for infected seed detection and practical field implications. Planting date and cultivar susceptibility significantly (P = <0.0001) affected disease incidence and severity. Late planting of a resistant wheat genotype resulted in ~90% less disease in the field with and consequently higher yield and seed quality. The combination of high rainfall accumulation (67.7 mm) and prolonged high relative humidity (>80% for 18 hrs.) during the heading stage was associated with epidemic blast development. A previously published study provided strong evidence of a positive correlation between disease incidence in the field and infection of wheat seeds. Given a uniform infected seeds distribution and fully efficient sampling method, the PCR detection threshold of 0.1% of MoT infected seeds in a seed sample represents up to 20 kg from a 20 metric tonnes harvest wagon will go undetected, equivalent to 6.66 x 10⁵ infected seeds. The calculated threshold for the Blotter test was equivalent to 1600 kg from a 20 metric tonnes or 5.3 x 10⁷ infected seeds will go undetected. Therefore, it is crucial to complement seed inspections with field assessments to decrease the likelihood of MoT dissemination through infected seeds to non-MoT established areas.
Keywords: Wheat blast